Meta-Analysis: Effectiveness of Husband's Support for Intrauterine Device Choice in Indonesia - Nuryuliana, Nuryuliana (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Intrauterine devices are an effective form of long-term contraception. Interventions involving husband support are expected to increase the interest of women of childbearing age in choosing an intrauterine device. This study aims to determine the effectiveness of husband support in choosing an intrauterine device in Indonesia. Subjects and Methods: A systematic review and meta-analysis were conducted using the PRISMA guidelines and the PICO model, including Population = women of childbearing age; Intervention = husband support; Comparison = no husband support; Outcome = choice of an intrauterine device. Articles were collected through a Health Journal database focused on Indonesia. The keywords used were: choice of IUD, husband support, Indonesia. A total of 11 articles met the inclusion criteria for the meta-analysis and were assessed using RevMan 5.3. Results: A meta-analysis of nine provinces in Indonesia showed that women of childbearing age who received husband support in choosing an intrauterine device were 12.30 times more likely to choose an intrauterine device than those who did not receive husband support, and this effect was statistically significant (OR= 12.30; 95% CI= 8.03 - 18.83; p <0.001). Conclusion: Husband support is highly effective in increasing the choice of an intrauterine device among women of childbearing age in Indonesia.